"Apa Khabar Malaysia" explores "Tanah Lidi" and Legal Status with Dr. Azhani binti Arshad - UiTM, Faculty of Law (Faculty of Law, 2023)
The episode of "Apa Khabar Malaysia" featuring Dr Azhani binti Arshad, a distinguished Senior Lecturer from the Faculty of Law· at Universiti Teknologi MARA (UiTM), served as an informative platfor for viewers to explore the enigmatic worlcl of "Tanah Lidi" and its IegaI status. Dr. Azhani's expertise and eIoquence added depth to the discussion, making it a valuable resource for those interested in legal matters. The program, which aired on Bernama TV at 9:00 AM, proved to be an enIightening experience, contributing to a greater understanding of this complex issue in the legal domain.